2013
DOI: 10.1111/eci.12162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bariatric surgery on echocardiographic indices: a review of the literature

Abstract: Obesity is the new epidemic and is associated with an increased risk of diastolic and systolic heart failure. Effective treatment options with drastic results such as bariatric surgery have raised interest in the possible reversal of some of the cardiovascular sequelae. Many studies have assessed individually the effect of weight loss on specific echocardiographic indices, mostly employing nonhomogeneous groups. The purpose of this narrative review is to summarise the effect of bariatric surgery on echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
(83 reference statements)
1
18
0
10
Order By: Relevance
“…For example, in the LOOK-AHEAD study substantial improvements in adiposity and increases in physical fitness in patients with diabetes were not associated with any reduction in heart failure [RRR 0.80 (95% CI 0.61-1.04, p=0.10] [33]. By contrast, more intensive weight loss achieved following bariatric surgery is associated with regression of cardiac hypertrophy and an increase of stroke volume and contractility [34]. Such interventions may be appropriate for selected patients with diabetes and heart failure, in whom post-operative risk is acknowledged and carefully managed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the LOOK-AHEAD study substantial improvements in adiposity and increases in physical fitness in patients with diabetes were not associated with any reduction in heart failure [RRR 0.80 (95% CI 0.61-1.04, p=0.10] [33]. By contrast, more intensive weight loss achieved following bariatric surgery is associated with regression of cardiac hypertrophy and an increase of stroke volume and contractility [34]. Such interventions may be appropriate for selected patients with diabetes and heart failure, in whom post-operative risk is acknowledged and carefully managed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]7,8,[19][20][21] Bariatric surgery has been more successful than diet ± exercise or pharmacotherapy in achieving regression of LVH and improvement in LV diastolic filling and systolic function (when impaired). [1][2][3][4][5][19][20][21][22][23][24] This presumably is related to greater weight loss which contributes to favorable changes in hemodynamics and LV loading conditions, a more favorable metabolic milieu, and improvement in sleep-disorder breathing.…”
Section: 24mentioning
confidence: 99%
“…[1][2][3][4][5]7,8,[19][20][21] Bariatric surgery has been more successful than diet ± exercise or pharmacotherapy in achieving regression of LVH and improvement in LV diastolic filling and systolic function (when impaired). [1][2][3][4][5][19][20][21][22][23][24] This presumably is related to greater weight loss which contributes to favorable changes in hemodynamics and LV loading conditions, a more favorable metabolic milieu, and improvement in sleep-disorder breathing. [1][2][3][4][5]7,[19][20][21][22] In addition, several small studies have demonstrated that substantial weight loss from bariatric surgery is capable of reversing clinical manifestations, improving New York Heart Association functional class, and enhancing quality of life in severely obese subjects with heart failure.…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Tais alterações hemodinâmicas podem induzir à hipertrofia do ventrículo esquerdo (VE) e à disfunção diastólica e sistólica desta câmara. [2][3][4] A hipertrofia do VE é um dos fatores de risco para a morbidade e mortalidade cardiovasculares. 5 A cirurgia bariátrica está associada à redução dos casos de mortalidade em geral.…”
Section: Introductionunclassified